AN INCREASE THE ACTIVITY OF THIRD GRADERS AT SDN BULAY 1 WITH TGT MODEL - annisak, elvy risky; Setyawan, Agung (Jurnal PGSD Indonesia, 2022)
This study aims to describe the increase in student learning activity in the Thematic lesson Theme 1 (Growth and Development of Living Things) Sub Theme 1 (Characteristics of Living Things) learning 5 class III SDN BULAY I through the application of cooperative learning model type TGT (Teams Games Tournament). The method in this study was carried out based on the flow in the CAR, which was carried out in 4 stages, namely planning, implementation, observation, and reflection which were carried out for 2 cycles.The sample used is class III SDN BULAY 1, totaling 19 people. The instrumens in this study were interview instruments and student learning activity instruments that had been provided previously. The results of this study indicate an increase in student learning activity in each cycle. This can be seen from the results of observations that have been made, in the first cycle the percentage of student learning activity is 79%. Then for the percentage of student learning activity in the second cycle, which is 98%.